(untitled) (AYUSHDHARA, 2019)
Drug Abuse is a patterned use of a drug in which the user consumes the substance in amounts or with methods which are harmful to themselves or others, and it is a form of substance –related disorder. Drug abuse can be abuse of any substance including cigarettes, alcohol, cannabis, cocaine, Heroin, tobacco and others. It is a serious public health problem that affects almost every community and family in some way. It plays a role in many major social problems, such as drugged driving, violence, stress and child abuse. It can lead to homelessness, crime and missed work or problems with keeping a job. It harms unborn babies and destroys families. In some cases criminal or anti – social behaviour occurs when the person is under the influence of a drug and long term personality changes in individual may occur. Indiscriminate use of drugs may produce mental, physical and moral deterioration of the individual and in some cases may lead to sexual perversion or crimes, use of some drugs may also lead to criminal penalties. During the last few decades the problem of drug abuse has almost reached epidemic proportions. A patient afflicted with the drug abuse should be first take careful history and then proper clinical examination we manage it using principles of Ayurveda i.e., Nidana Parivarjan/preventive measure, Padanshik kram for abuse drug, detoxification, Siro Dhara, Sirolepa, Yoga, Meditation, rehabilitation and using supplementary medication as mention in our classical text.